1953
DOI: 10.1104/pp.28.2.201
|View full text |Cite
|
Sign up to set email alerts
|

Floral Induction and Development in Ochard Grass

Abstract: PETERSON and LooMis (11) found that both low temperature and short day lengths were necessary for floral induction in Kentucky bluegrass, but growth and development of flowers were favored by long days and a moderately warm temperature. Other investigators (8, 9) have obtained similar results with smooth brome grass. COOPER (2) found that perennial rye grass remained vegetative under continuous illumination in a warm greenhouse, whereas annual and Italian types flowered well under these conditions.From a physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

1954
1954
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(20 citation statements)
references
References 10 publications
2
17
1
Order By: Relevance
“…On the other hand, 30 December sowing received higher day/night temperature that hastens forced maturity and reduced TDM production and translocation to the yield components. Similar results were recorded by Peterson and Loomis (1949) in Kentucky bluegrass, Gardner and Loomis (1953) in orchard grass, Lindsey and Peterson (1964) in Poa pratensis L. Seed yield is the function of pods/plant, seeds/pod and 1000-seed weight. Date of sowing significantly influenced the seed yield/ha of garden pea.…”
Section: Fig 1 Effect Of Sowing Dates On Leaf Area Index Of Bari Mosupporting
confidence: 69%
“…On the other hand, 30 December sowing received higher day/night temperature that hastens forced maturity and reduced TDM production and translocation to the yield components. Similar results were recorded by Peterson and Loomis (1949) in Kentucky bluegrass, Gardner and Loomis (1953) in orchard grass, Lindsey and Peterson (1964) in Poa pratensis L. Seed yield is the function of pods/plant, seeds/pod and 1000-seed weight. Date of sowing significantly influenced the seed yield/ha of garden pea.…”
Section: Fig 1 Effect Of Sowing Dates On Leaf Area Index Of Bari Mosupporting
confidence: 69%
“…Langer (5) reports that in the S.48 strain of timothy neither short days nor low temperature is normally necessary for floral induction. This is supported by field results, such as those of Stapledon and Wheeler (7) in Britain, and Gardner and Loomis (3) in Iowa, in which timothy readily formed heads after spring sowing. MATERIAL The eight strains used in this investigation are listed below; all except S.50 are strains of hexaploid P. pratense …”
Section: Introductionsupporting
confidence: 67%
“…Based on experiments showing no transmission of the induced stage within seeds of Dactylis glomerata , Gardner & Loomis (1953) concluded that each tiller has to be primary induced directly in order to become reproductive. Similar conclusions were drawn by other investigators (e.g.…”
Section: Transfer Of Flower Induction Stimuli To Non-exposed Tillers mentioning
confidence: 98%